The April –May 2010 Eyjafjallajokull eruption (Iceland): tephra characteristics, eruption dynamics, and role of magma-ice-water interaction - CIONI, RAFFAELLO; PISTOLESI, MARCO (GeoItalia, 2011)
Abstract su vulcano Islandese per congresso FIST 2011